Formulasi Sediaan Mouthwash Ekstrak Daun Sirih Hitam (Piper sp.) Terhadap Streptococcus mutans dan Candida albicans: Mouthwash Preparation Formulation of Black Betel Leaf Extract (Piper sp.) Against Streptococcus mutans and Candida albicans - Deschania Noor Qhorina; Fajar Prasetya; Mirhansyah Ardana (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Black betel (Piper sp.) contains compounds that function as antimicrobials, namely tannins, phenolic compounds, saponins, flavonoids, alkaloids, and steroids that can be used as active ingredients for making mouthwash. The purpose of this study was to determine the effective mouthwash formulation used as an antimicrobial. Antimicrobial testing method using well diffusion method with a reserve of 6 mm. Black betel leaf extract was dissolved with a variation of the concentration of glycerin 1:4; 1:8 and 1:12 and tested on Streptococcus mutans and Candida albicans bacteria, then tested for stability of the preparations, including organoleptic, pH and viscosity. The results obtained from various solvents were glycerin as the most stable solvent compared to 96% ethanol, tween 80 and aquades. The results obtained from the antimicrobial test with ANOVA analysis were for Streptococcus mutans bacteria p=0.004 (p<0.05) which means the p-value was significant between concentration variations and bacteria and for the fungus Candida albicans p=0.295 (p>0.05) which meant the p-value was not significant difference between concentration variations and fungi. The results of the evaluation test for the stability of the preparation, namely the organoleptic data, pH and viscosity at a temperature of 25ºC were relatively stable.